Median and ulnar nerve functions in taxi/microbus drivers and helpers in Kathmandu - Amatya, Mrigendra; Khanal, Bibek (Journal of Kathmandu Medical College, 2020)
Background: Occupational drivers are exposed to various stressors such as ergonomic restriction, whole body vibration, vehicle exhaust and dust exposure. Drivers are reported to have higher rates of morbidities, especially of the musculoskeletal and peripheral nervous systems. Reports on drivers’ nerve functions by specific electrodiagnostic methods are lacking. Objectives: To compare electrophysiologic parameters of median and ulnar nerves in drivers with other population. Methodology: In a cross-sectional comparative study, nerve conduction study was performed in median and ulnar nerves in three groups of participants – Drivers (driving taxi/microbus for at least six months), Helpers (microbus conductors for at least six months) and Controls (college staff/students). Parameters for sensory nerve action potentials and compound motor action potentials were compared among groups by ANOVA and right versus left sides within groups by paired t test. Results: The study involved 145 male participants – 51 Drivers, 34 Helpers and 60 Controls. Compared to drivers and helpers, conduction velocity of nerves was significantly higher in controls for sensory component of all nerves (p values for right median = 0.001, left median = <0.001, right ulnar = <0.001 and left ulnar = 0.019) and motor component of right ulnar nerve (p=0.002). In right-left comparisons, conduction was slower in left median sensory than right (p=0.001) and right ulnar sensory than left (p=0.015) in the helpers but not significant in other groups. Conclusion: Electrophysiological evidences of afflictions of median and ulnar nerves are detectable in urban taxi/ microbus drivers and helpers with at least six months’ occupational duration.